APPLICATION OF TECHNOLOGY IN ISLAMIC EDUCATION MANAGEMENT - Uuh Buchori; E. Syarifudin; Eneng Muslihah (INCARE, International Journal of Educational Resources, 2023)
The important role of Islamic education in shaping the noble character of the nation's younger generation is widely acknowledged. In the era of information and communication technology, these advancements have transformed various aspects of human life, including education. The implementation of technology in Islamic education management holds the potential for significant benefits, such as enhancing school administration efficiency. This study utilizes a qualitative research method to gain a comprehensive understanding of the application of technology in Islamic education management at MAN 4 Pandeglang. Data is collected through interviews, observations, and document analysis to ensure a deep comprehension of the subject matter. The research findings demonstrate that the application of technology in Islamic education management at MAN 4 Pandeglang has yielded significant impacts. The utilization of information and communication technology (ICT) in school administration has enhanced the efficiency and effectiveness of educational management. Moreover, the adoption of e-learning, mobile applications, and multimedia technology has improved the quality of Islamic education and increased student and teacher engagement in the educational process. In order to ensure sustainability, the implementation of technology needs to be continuous, enabling MAN 4 Pandeglang to develop a modern, efficient, and effective educational environment. This endeavor will help provide high-quality Islamic education to students and strengthen the school's role in promoting the values of Islam, which are good and righteous.